Antibody immobilization on poly(L-lactic acid) nanofibers advantageously carried out by means of a non-equilibrium atmospheric plasma process. (15th June 2016) - Dolci, L S; Liguori, A; Merlettini, A; Calzà, L; Castellucci, M; Gherardi, M; Colombo, V; Focarete, M L
Abstract: In the present study, the comparison between a conventional wet-chemical method and a non-equilibrium atmospheric pressure plasma process for the conjugation of biomolecules on the surface of poly(L-lactic acid) (PLLA) electrospun fibers is reported. Physico-chemical and morphological characteristics of chemically and plasma functionalized mats are studied and compared with those of pristine mats. The efficiency in biomolecules immobilization is assessed by the covalent conjugation of an antibody (anti-CD10) on the functionalized PLLA fibers. The achieved results highlight that the proposed plasma process enables antibodies to be successfully immobilized on the surface of PLLA fibers, demonstrating that non-equilibrium atmospheric pressure plasma can be an effective, highly flexible and environmentally friendly alternative to the still widely employed wet-chemical methods for the conjugation of biomolecules onto biomaterials.